Caryopteris odorata and its metabolite coumarin attenuate characteristic features of cardiometabolic syndrome in high-refined carbohydrate-high fat-cholesterol-loaded feed-fed diet rats - Ahmed, Mobeen Ghulam; Mehmood, Malik Hassan; Mehdi, Shumaila; Farrukh, Maryam (Frontiers in Pharmacology, 2023)
Caryopteris odorata (D. Don) B.L. Robinson (Verbenaceae family) is traditionally used to treat diabetes and related pathologies (diabetic foot ulcer), cancer/tumor, wound healing and inflammation. It is enriched with flavonoids and phenolics like coumarins, quercetin, gallic acid, coumaric acid, stigmasterol, α-tocopherol and Iridoids. C. odorata has been reported for its α-glucosidase, anti-inflammatory and anti-oxidant activities. Its effectiveness in prevention of cardiometabolic syndrome has not been accessed yet. Thisstudy aims to investigate the potential role of C. odorata and Coumarin for characteristic features of cardiometabolic syndrome (CMS) including obesity, dyslipidemia, hyperglycemia, insulin resistance and hypertension using high refined carbohydrate-high fat- cholesterol (HRCHFC) loaded feed-fed rats. Chronic administration of C. odorata and Coumarin for 6 weeks, showed a marked attenuation in body and organ weights with consistent decline in feed intake compared to HRCHFC diet fed rats. Test materials caused a significantly reduction in blood pressure (systolic, diastolic and mean) and heart rate of HRCHFC diet fed rats. Improvement in glucose tolerance and insulin sensitivity tests were also observed in test material administered rats compare to only HRCHFC diet fed rats. C. odorata and Coumarin treated animals produced a marked decline in serum FBG, TC, TG, LFTs and RFTs, while an increase in serum HDL-C levels was noticed. C. odorata and Coumarin also significantly modulated inflammatory biomarkers (TNFα, IL-6), adipokines (leptin, adiponectin and chemerin) and HMG-CoA reductase levels, indicating prominent anti-inflammatory, cholesterol lowering and anti-hyperglycemic potential. Administration of C. odorata and Coumarin exhibited a marked improvement in oxidative stress markers (CAT, SOD, MDA). Histopathological analysis of liver, heart, kidney, pancreas, aorta and fat tissues showed revival of normal tissue architecture in C. odorata and Coumarin treated rats compared to HRCHFC diet fed rats. These results suggest that C. odorata and Coumarin possess beneficial effects against characteristic features (obesity, insulin resistance, hypertension, dyslipidemia) of CMS in HRCHFC feed administered rats. These effects were possibly mediated through improvement in adipokines, glucose tolerance and insulin sensitivity, attenuation of HMG-CoA reductase and inflammatory biomarkers and modulation in oxidative stress biomarkers. This study provides a rationale to the therapeutic potential of C. odorata and Coumarin in CMS.